Income Dynamics and the Affordable Care Act - Shore-Sheppard, Lara D (Health Serv Res, 2014)
OBJECTIVE: To examine the sources of family income dynamics leading to movement into and out of Medicaid expansion and subsidy eligibility under the Affordable Care Act. DATA SOURCE: Survey of Income and Program Participation (SIPP): 1996, 2001, 2004, 2008 panels. STUDY DESIGN: Considering four broad subsidy eligibility categories for monthly Modified Adjusted Gross Income (MAGI) (<138 percent of the Federal Poverty Level [FPL], 138–250 percent FPL, 250–400 percent FPL, and >400 percent FPL), I use duration analysis to examine determinants of movements between categories over the course of a year. DATA COLLECTION/EXTRACTION: Using detailed monthly data, I determine the members of tax-filing units and calculate an approximation of MAGI at the monthly level. The analysis sample is adults ages 22–64 years. PRINCIPAL FINDINGS: Incomes are highly variable within a year, particularly at the lower end of the income distribution. Employment transitions, including transitions not involving a period of nonemployment, and family structure changes strongly predict sufficient income volatility to trigger a change in subsidy category. CONCLUSIONS: Income volatility arising from employment and family structure changes is likely to trigger changes in subsidy eligibility within the year, but the sources and effects of the volatility differ substantially depending on the individual's position in the income distribution.